Piezoelectric Energy Harvesting Using A 10x10 Sensor Matrix with Integrated Circuit Design for Pressure Control - Siddharth Borghe; Kapil Sangameshwar; Dhruvesh Kamble; Santosh Kandhare (International Journal of VLSI Circuit Design & Technology, 2024)
This project aims to create a system that generates energy using piezoelectric technology, designed as a rectangular tile platform. The platform has two layers of sensors arranged in a 10 × 10 grid, connected in a mix of series and parallel setups. The top layer acts as a surface for external forces, like footsteps, while springs connect the layers to control pressure and maximize energy generation. A rectifier ensures the energy output is stable, and capacitors store the collected energy for later use. Tests show the system is effective at turning pressure into usable energy, with the springs helping it reset after each use. This study primarily aims to evaluate how viable and efficient piezoelectric energy harvesting systems are as a consistent power source for low-power electronic devices. It also seeks to expand knowledge about the environmental sustainability and impact of these systems, supporting the broader goal of advancing renewable energy technologies for a more sustainable future. This innovative design is scalable and sustainable, making it ideal for powering small electronic devices and promoting eco-friendly energy solutions.
Keywords: Piezoelectric sensors; full-wave rectifier; load; rechargeable battery